2010
DOI: 10.1016/j.cmet.2010.04.016
|View full text |Cite
|
Sign up to set email alerts
|

GPIHBP1 Is Responsible for the Entry of Lipoprotein Lipase into Capillaries

Abstract: SUMMARY The lipolytic processing of triglyceride-rich lipoproteins by lipoprotein lipase (LPL) is the central event in plasma lipid metabolism, providing lipids for storage in adipose tissue and fuel for vital organs such as the heart. LPL is synthesized and secreted by myocytes and adipocytes but then finds its way into the lumen of capillaries, where it hydrolyzes lipoprotein triglycerides. The mechanism by which LPL reaches the lumen of capillaries represents one of the most persistent mysteries of plasma l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
414
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 316 publications
(440 citation statements)
references
References 23 publications
(42 reference statements)
10
414
0
3
Order By: Relevance
“…The protein GPIHBP1 binds to the endothelium of capillary cells where it provides a platform for LPL to process triglycerides from lipoproteins (41). GPIHBP1 also helps transport LPL across the endothelial cells, and a recent study has shown that this transport is bidirectional (25,42). ANGPTL4 could thus inhibit LPL in either the subendothelial space or on the surface of the capillary endothelium, and a number of recent studies support the former option.…”
Section: Discussionmentioning
confidence: 85%
“…The protein GPIHBP1 binds to the endothelium of capillary cells where it provides a platform for LPL to process triglycerides from lipoproteins (41). GPIHBP1 also helps transport LPL across the endothelial cells, and a recent study has shown that this transport is bidirectional (25,42). ANGPTL4 could thus inhibit LPL in either the subendothelial space or on the surface of the capillary endothelium, and a number of recent studies support the former option.…”
Section: Discussionmentioning
confidence: 85%
“…To stain blood vessels, FITC-labeled tomato lectin (Vector Laboratories) was injected i.v. into mice as described (17). Epifluorescence microscopy images were obtained with an Axiovert 200MOT microscope equipped with an ApoTome, and processed with Axiovert 4.6 software (all from Zeiss).…”
Section: Methodsmentioning
confidence: 99%
“…Rat heart microvascular endothelial cells transduced with a GPIHBP1 lentivirus were grown on fibronectin-coated Millicell filters (polyethylene terephthalate, 1.1 cm 2 filtration area, 1 μm pore size; Millipore) until they formed tight monolayers (11). After adding V5-tagged LPL to the basolateral chamber and PBS solution to the apical chamber, the cells were incubated at 37°C for 1 h. The LPL transported to the apical surface of cells was released with heparin (100 U/mL for 5 min) and quantified as described previously (11). Transport was also assessed by microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…LPL is synthesized by myocytes and adipocytes and secreted into the interstitial spaces, but is then transported to the capillary lumen by GPIHBP1, a GPI-anchored protein of endothelial cells (10,11). An absence of GPIHBP1 abolishes the entry of LPL into capillaries, causing severe chylomicronemia and an accumulation of catalytically active LPL in the interstitial spaces (11).…”
mentioning
confidence: 99%